Choroidal Neovascularisation Complicating Chronic Central Serous Chorioretinopathy: The Discovery Rate on Multimodal Imaging - Romdhane, Khaled; Mantel, Irmela (Klinische Monatsblätter für Augenheilkunde, 2019)
Purpose To identify the image modality allowing identification of choroidal neovascularisation (CNV) complicating chronic central serous chorioretinopathy (CSCR), including fluorescein angiography (FA), indocyanine green angiography (ICGA), and optical coherence tomography angiography (OCT-A).Methods Patients diagnosed with chronic CSCR and secondary CNV were included in the study. The image modalities FA, ICGA, and OCT-A were reviewed for specific CNV signs permitting diagnosis. Patients with missing image modalities, poor image quality, previous laser treatment, or other confounding pathologies were excluded.Results CNV was identified on OCT-A in 32 of 33 eyes (97%), whereas ICGA revealed an abnormal vascular network in 23 eyes (70%), significantly less frequently than with OCT-A (p = 0.003). FA allowed CNV identification in 10 eyes (30%), significantly less frequently than with OCT-A (p < 0.001). Type 1 CNV was detected by OCT-A in 29 of 30 eyes (97%), by ICGA in 20 eyes (67%; p = 0.0027), and by FA in 8 eyes (27%; p < 0.001).Conclusions OCTA is a useful diagnostic tool to detect occult CNV complicating chronic CSCR. This image modality might be important for adequate patient care.
Keywords: central serous chorioretinopathy; choroidal neovascularisation; optical coherence tomography angiography